The Bibliometric Analysis of Fraud Reporting: Scientific Publications from 2019 to 2024 - Fajriyati, Sausan; Yusuf, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the development of scientific publications related to fraud reporting during the period of 2019–2024. Using a quantitative method based on a bibliometric study approach, data was collected from the Scopus database with the keywords